SmartCopter: Enabling autonomous flight in indoor environments with a smartphone as on‐board processing unit. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The authors present a low‐cost unmanned aerial vehicle (UAV) for autonomous flight and navigation in GPS‐denied environments using an off‐the‐shelf smartphone as its core on‐board processing unit. Thereby, the approach is independent from additional ground hardware and the UAV core unit can be easily replaced with more powerful hardware that simplifies setup updates as well as maintenance. The paper aims to discuss these issues.Design/methodology/approach – The UAV is able to map, locate and navigate in an unknown indoor environment fusing vision‐based tracking with inertial and attitude measurements. The authors choose an algorithmic approach for mapping and localization that does not require GPS coverage of the target area; therefore autonomous indoor navigation is made possible.Findings – The authors demonstrate the UAVs capabilities of mapping, localization and navigation in an unknown 2D marker environment. The promising results enable future research on 3D self‐localization and dense mapping using mobile hardware as the only on‐board processing unit.Research limitations/implications – The proposed autonomous flight processing pipeline robustly tracks and maps planar markers that need to be distributed throughout the tracking volume.Practical implications – Due to the cost‐effective platform and the flexibility of the software architecture, the approach can play an important role in areas with poor infrastructure (e.g. developing countries) to autonomously perform tasks for search and rescue, inspection and measurements.Originality/value – The authors provide a low‐cost off‐the‐shelf flight platform that only requires a commercially available mobile device as core processing unit for autonomous flight in GPS‐denied areas.